Ready, set, blast off! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack, 2017)
"Picked to represent their planet Nebulon in the Interstellar Space Race, Zack and his friends navigate their specially designed car through an underwater maze, around planetary rings, and through the stars! But when trouble stirs within the team, Zack must take charge. Can he lead them to victory?"--